Mingle Game To Improve Students’ Speaking Ability At The Seventh Grade Students Of SMP Pangudi Luhur Sukaraja - Annisa Fatmalati; Zulaikah Zulaikah; Muhammad Zainuddin Afas (Lembaga Pengembangan Kinerja Dosen, 2023)
The objective of the research was to find out whether or not there is any significant difference between students who are taught by using Mingle Game and students who are not taught by using Mingle Game in speaking ability at the seventh grader of SMP Pangudi Luhur Sukaraja. The population of the research was the seventh grade students’ of SMP Pangudi Luhur Sukaraja consist of 44 students and the sample consist of 22 students. The sample of this research was taken by purposive sampling. The method of this research was quantitative method and the design was quasi experimental design. The instrument of this research was used oral test. The value of t-obtain = 8.492 is higher than t-table = 2.021. The value of sig (2 tailed) = 0.00 less than the value significant level (0.05). Finally the researcher concluded that Alternative Hypothesis (Ha) of this study was accepted and Null Hypothesis (H0) of this study was rejected.